The relationships between perceived individual and team characteristics, individual and team learning activities with effectiveness in nursing teams - Anselmann, Veronika; Brouwer, Jasperina; Mulder, Regina H. (Frontiers in Psychology, 2023)
Introduction Team learning plays a crucial role in addressing the shortage of nurses and ensuring that there are enough trained and capable nurses available during times of crisis. This study investigates the extent to which individual learning activities (1) contribute to knowledge sharing in teams and (2) impact the effectiveness of nursing teams. Furthermore, we want to obtain more insight into whether (3) the antecedents of individual psychological empowerment, teamwork preference, and team boundedness contribute to individual learning activities and knowledge sharing in nursing teams. Method We conducted a cross-sectional questionnaire study of 149 gerontological nurses working in 30 teams in Germany. They completed a survey measuring knowledge sharing, teamwork preference, team boundedness, individual learning activities, psychological empowerment, and team effectiveness (as an indicator of performance). Results The results from structural equation modeling revealed that individual learning activities contribute to knowledge sharing in teams and, as a result, enhance team effectiveness. In particular, psychological empowerment was found to be associated with individual learning activities, while teamwork preference and team boundedness were related to knowledge sharing. Discussion The results indicated that the accomplishment of individual learning activities plays an important role in nursing teams, as it is linked to knowledge sharing and, as a result, contributes to team effectiveness.